2020
DOI: 10.37899/journallalifesci.v1i4.203
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of Climate Smart Agricultural Practices by Rice Farmers in Akwa Ibom State, Nigeria

Abstract: The rise in population amidst climate change has exerted undue pressure on food production and security. Rice production has also been adversely affected by rising temperature and varying rainfall resulting in reduced productivity. In order to cope with the negative impact of climate change events on rice production, farmers need strengthen and improve their adaptive capacity. Therefore, a study was conducted to empirically estimate the factors affecting the adoption of Climate Smart Agricultural ( CSA) practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 10 publications
2
6
1
Order By: Relevance
“…Majority (92.5%) of the farmers were married. This result conforms to that of Etim and Ndaeyo (2020), who found that majority (75%) of rice farmers were married. The average number of years spent in school was 8.7 years.…”
Section: Socioeconomic Characteristics Of the Farmerssupporting
confidence: 91%
“…Majority (92.5%) of the farmers were married. This result conforms to that of Etim and Ndaeyo (2020), who found that majority (75%) of rice farmers were married. The average number of years spent in school was 8.7 years.…”
Section: Socioeconomic Characteristics Of the Farmerssupporting
confidence: 91%
“…This result corroborates that of Ojo et al, (2021) which pointed out that marital status negatively influenced the adoption of soil water conservation technologies as large families may be resource constrained. The finding, however, contradicts those of Etim and Ndaeyo (2020) who noted that marriage is a means of generating family labour and most women and children participate in farming. Furthermore, marriage increases concern for household welfare and food security therefore, use of new technologies was positively related to marital status.…”
Section: Support Required By Farming Households To Increase Uptake Of...contrasting
confidence: 87%
“…The dichotomous nature of the dependent variable necessitated the use of probit regression model to quantitatively estimate the factors that influence the decision of farmers to participate in cooperative organizations. The probit model is suitable for analyzing decision that have dichotomous values (Etim et al,2017;Etim et al,2020c;Etim and Ndaeyo, 2020;Etim and Udoh,2020). Its ability to resolve the problem of heteroscedasticity and also limit the utility value of the decision to join variable to lie between 0 and 1, makes it preferable to the logit model (Asante et al, 2011;Martey et al,2014).…”
Section: Model Specificationmentioning
confidence: 99%